PENGGUNAAN MEDIA KOMIK MELALUI METODE LEARNING STARTS WITH A QUESTIONN DALAM MENINGKATKAN HASIL BELAJAR - Henny Zurika (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This study aims to improve student learning outcomes through the use of media accounting comics through "Learning starts with a question" on the subject of preparing the financial statements.